A new hydrocarbon empirical potential for molecular dynamics simulation - Tan, Ai Ping (2017)
Molecular dynamics utilize energy model to solve the Newton’s equation of motion for a system of interacting particles. Ab-initio, semi-empirical and empirical approaches have been reported as main approaches to compute total energy of a system for describing its molecular structures and properties. In these approximation methods, the calculations achieved the level of accuracy in descending manner and in ascending order for computational time. Ab-initio approach also known as first principles method solved the complex energy evaluations in Schrödinger equation to account for electronic structures with limitation on the size of the system. Molecular mechanics (MM) is a conventional empirical approach that defined energy calculations in terms of functions with fitted parameters. The simple algorithm in MM allowed it to simulate larger system. Consequently, new potential function is always required either to produce higher accuracy result or to reduce the computational time. It is believed that there should be a compromise between the accuracy and the computational time depending on the simulation. The main contribution of this study is to propose a new hydrocarbon potential energy model which consist of bond stretching and angle bending function, where both functions are important components of short range potential for the force fields based on MM principle. The existing bond stretching and angle bending functions are found correlated to the piecewise polynomial concept. New models were then proposed based on piecewise polynomial concept and basic principles. Firstly, by neglecting the motion of electrons for fast computation purpose. Secondly, only the necessity independent variables are involved. Thirdly, structural properties such as symmetry and degeneracy are considered. In this regard, the interatomic distance was determined as the independent variable in bond stretching model since single independent variable is assumed sufficient in reproducing the chemical reaction for one motion involvement. Angle was selected as independent variable when the interactions were treated as a plane with triangle shape. However, there is more than one motion involvement in angle bending model, thus, the deviation for angle is also considered as independent variable. The selection rules were developed and independent variables were coupled with the interatomic distance to account for structural properties. Hence, the angle bending model is developed based on the triangle and selection rules. The parameters were estimated by using least square method. The proposed model was then compared with data collected from two well-established methods and applied to the carbon nanotube application for validation. Most of the results obtained achieved a good agreement except for carbon nanotube application where the discussions were given. Good agreement with data collection indicates that proposed models can be alternative solution to the existing force fields. The results are significant for advancement of new knowledge.